Hubungan Perceived Social Support dengan Academic Stress pada Mahasiswa - Nabel Prasetya Ersada Tarigan; Utami Syah Brianti; Nahila Nusaiba; Lucky Purwantini (Universitas Palangka Raya, 2026)
College students are frequently exposed to psychological pressure stemming from heavy academic workloads and intense grade competition. This study aims to examine the correlation between perceived social support and academic stress, while exploring disparities in stress levels based on student demographic profiles in Indonesia. Utilizing a quantitative correlational and comparative design, data were gathered from 1,062 participants through convenience sampling. The research employed the Multidimensional Scale of Perceived Social Support (MSPSS) and the Educational Stress Scale for Adolescents (ESSA), with data analyzed using Spearman’s rho correlation and non-parametric difference tests. The findings indicate a significant but very weak negative relationship between perceived social support and academic stress (r = -0.119;p = 0.001). Descriptive data revealed that 53.62% of respondents experienced high academic stress despite reporting strong social support. Comparative analysis showed significantly higher stress levels among non-scholarship students, overseas students dealing with homesickness, those involved solely in academic activities, and students living with grandparents. These results suggest that academic stress is a multifaceted phenomenon influenced not only by external support systems but also by internal determinants such as self-efficacy, self-esteem, and self-regulation skills.